[177Lu]-PSMA-617 radionuclide treatment in patients with metastatic castration-resistant prostate cancer (LuPSMA trial): a single-centre, single-arm, phase 2 study. Issue 6 (June 2018) - Hofman, Michael S; Violet, John; Hicks, Rodney J; Ferdinandus, Justin; Thang, Sue Ping; Akhurst, Tim; Iravani, Amir; Kong, Grace; Ravi Kumar, Aravind; Murphy, Declan G; Eu, Peter; Jackson, Price; et al.
Summary: Background: Progressive metastatic castration-resistant prostate cancer is a highly lethal disorder and new effective therapeutic agents that improve patient outcomes are urgently needed. Lutetium-177 [ 177 Lu]-PSMA-617, a radiolabelled small molecule, binds with high affinity to prostate-specific membrane antigen (PSMA) enabling beta particle therapy targeted to metastatic castration-resistant prostate cancer. We aimed to investigate the safety, efficacy, and effect on quality of life of [ 177 Lu]-PSMA-617 in men with metastatic castration-resistant prostate cancer who progressed after standard treatments. Methods: In this single-arm, single-centre, phase 2 trial, we recruited men (aged 18 years and older) with metastatic castration-resistant prostate cancer and progressive disease after standard treatments, including taxane-based chemotherapy and second-generation anti-androgens, from the Peter MacCallum Cancer Centre, Melbourne, VIC, Australia. Patients underwent a screening PSMA and FDG-PET/CT to confirm high PSMA-expression. Eligible patients had progressive disease defined by imaging (according to Response Evaluation Criteria In Solid Tumours [RECIST] or bone scan) or new pain in an area of radiographically evident disease, and were required to have an Eastern Cooperative Oncology Group (ECOG) performance status score of 2 or lower. Eligible patients received up to four cycles of intravenous [ 177 Lu]-PSMA-617, at six weekly intervals. The primary endpoint was PSA response according to Prostate Cancer Clinical Trial Working Group criteria defined as a greater than 50% PSA decline from baseline and toxicity according to CTCAE. Additional primary endpoints were imaging responses (as measured by bone scan, CT, PSMA, and FDG PET/CT) and quality of life (assessed with the EORTC-Q30 and Brief Pain Inventory-Short Form questionnaires), all measured up to 3 months post completion of treatment. This trial is registered with the Australian New Zealand Clinical Trials Registry, number 12615000912583. Findings: Between Aug 26, 2015, and Dec 8, 2016, 43 men were screened to identify 30 patients eligible for treatment. 26 (87%) had received at least one line of previous chemotherapy (80% docetaxel and 47% cabazitaxel) and 25 (83%) received prior abiraterone acetate, enzalutamide, or both. The mean administered radioactivity was 7·5 GBq per cycle. 17 (57%) of 30 patients (95% CI 37–75) achieved a PSA decline of 50% or more. There were no treatment-related deaths. The most common toxic effects related to [ 177 Lu]-PSMA-617 were grade 1 dry mouth recorded in 26 (87%) patients, grade 1 and 2 transient nausea in 15 (50%), and G1–2 fatigue in 15 (50%). Grade 3 or 4 thrombocytopenia possibly attributed to [ 177 Lu]-PSMA-617 occurred in four (13%) patients. Objective response in nodal or visceral disease was reported in 14 (82%) of 17 patients with measurable disease. Clinically meaningful improvements in pain severity and interference scores were recorded at all timepoints. 11 (37%) patients experienced a ten point or more improvement in global health score by the second cycle of treatment. Interpretation: Our findings show that radionuclide treatment with [ 177 Lu]-PSMA-617 has high response rates, low toxic effects, and reduction of pain in men with metastatic castration-resistant prostate cancer who have progressed after conventional treatments. This evidence supports the need for randomised controlled trials to further assess efficacy compared with current standards of care. Funding: None.